Instytucja doręczenia pism pełnomocnikowi w orzecznictwie sądów administracyjnych - Majewski, Kamil (Kwartalnik Prawa Publicznego, 2015)
This article provides an overview and analysis of the case law of the administrative courts in the field of service institutions in situations where proceedings page works through a proxy. In the first part shows the adjustment of power of Attorney and the characteristics of this institutions, with particular regard to its scope and the effects of what it calls the legal situation in respect of the parties to the proceedings and the investigating authority. In the part of the relevant effects are discussed the establishment of a representative for service. Outlined steps to be made to the service was legally effective. Regulation were analysed in view of fulfilling its enforcement in practice, the protection function and guarantees arising from the General principles of Polish Administrative Procedure Code.